The Effect Of The Combination Of Task Repetition And Post -task Transcribing On Students’ Fluency In Speaking English - Haq, Afdanil; Yelfiza, Yelfiza; Ikhsan, M.Khairi (Jurnal Pendidikan Tambusai, 2022)
This research was quantitative research that aimed to find out how the development of students' speaking fluency when the teacher applied the combination of task repetition and post-task transcribing in the speech class at Universitas PGRI Sumatra Barat. The technique of data collection was purposive sampling. research instruments were a video recorder and document. The researcher used the speech rate indicator (the number of syllables produced in one minute) to know students' speaking fluency. From the research data, it was found that the average of students' speech rate is increasing in each meeting and the speaking level of students remained at a slow level. Based on data analysis and discussion, the researcher concluded that the combination of task repetition and post-task transcribing was not very effective in improving students' speaking fluency in English because not all students increased their speech rate in each meeting.